2020
DOI: 10.31236/osf.io/gjbmx
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Doping prevalence in competitive sport: Evidence synthesis with “best practice” recommendations and reporting guidelines from the WADA Working Group on Doping Prevalence

Abstract: The primary aim of this subject- wide systematic review was to collate and synthesize evidence on doping prevalence from published scientific papers. Secondary aims involved reviewing the reporting accuracy and data quality as evidence for doping behavior to (1) develop quality and bias assessment criteria to facilitate future systematic reviews; and (2) establish recommendations for reporting future research on doping behavior in competitive sports to facilitate better meta-analyses of doping behavior. Using … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 25 publications
0
12
1
Order By: Relevance
“…The ADOs are encouraged to carefully consider the spectrum of these various parameters and identify the extent of how these will inform the development of their balanced TDP. Identifying the real doping prevalence remains the holy grail quest in the anti‐doping field 33 . Conducting an effective doping prevalence assessment is challenging for many reasons.…”
Section: Discussionmentioning
confidence: 99%
“…The ADOs are encouraged to carefully consider the spectrum of these various parameters and identify the extent of how these will inform the development of their balanced TDP. Identifying the real doping prevalence remains the holy grail quest in the anti‐doping field 33 . Conducting an effective doping prevalence assessment is challenging for many reasons.…”
Section: Discussionmentioning
confidence: 99%
“…Research has identified a range of motivations across competitive levels 25 , though at the elite levels of sport, money was identified as a primary factor 26,27 , making the drive to win greater than fear of the associated risks. Real prevalence of doping is impossible to measure, and estimates vary widely and may be flawed 28 . However, prevalence models routinely show doping rates of 10-60% depending on country, sport and level [29][30][31] .…”
Section: Why Do Athletes Dope?mentioning
confidence: 99%
“…A network of national anti-doping organizations (NADOs) and anti-doping laboratories now cooperate under the umbrella of WADA. This collective effort has led to sizable changes in doping behavior and prevalence 28 . These well-intended anti-doping efforts have surely changed athletes' doping patterns and how doping is perceived by athletes and the public.…”
Section: Twenty Years Of Wadamentioning
confidence: 99%
See 2 more Smart Citations